2023
DOI: 10.1039/d3nr03428c
|View full text |Cite
|
Sign up to set email alerts
|

Two molecule force spectroscopy on ligand–receptor interactions

Jiacheng Zuo,
Hui Chen,
Hongbin Li

Abstract: Two-molecule force spectroscopy enables the probing of the unbinding of two parallel ligand-receptor pairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…However, these formulas are limited by either zero external force or a two-bond cluster. At the same time, several studies have been conducted to intensively examine the dynamic strength of adhesion clusters. For example, in terms of theory, Friddle et al proposed a model to predict the measurement strength of a single/multiple molecular bonds. They found that the loading rate and stiffness of the loading device will significantly affect the fracture force of single-/multibond.…”
Section: Introductionmentioning
confidence: 99%
“…However, these formulas are limited by either zero external force or a two-bond cluster. At the same time, several studies have been conducted to intensively examine the dynamic strength of adhesion clusters. For example, in terms of theory, Friddle et al proposed a model to predict the measurement strength of a single/multiple molecular bonds. They found that the loading rate and stiffness of the loading device will significantly affect the fracture force of single-/multibond.…”
Section: Introductionmentioning
confidence: 99%